2011
DOI: 10.1038/npp.2011.200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cocaine Vaccine Linked to a Disrupted Adenovirus Gene Transfer Vector Blocks Cocaine Psychostimulant and Reinforcing Effects

Abstract: Immunotherapy is a promising treatment for drug addiction. However, insufficient immune responses to vaccines in most subjects pose a challenge. In this study, we tested the efficacy of a new cocaine vaccine (dAd5GNE) in antagonizing cocaine addiction-related behaviors in rats. This vaccine used a disrupted serotype 5 adenovirus (Ad) gene transfer vector coupled to a third-generation cocaine hapten, termed GNE (6-(2R,3S)-3-(benzoyloxy)-8-methyl-8-azabicyclo [3.2.1] octane-2-carboxamido-hexanoic acid). Three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 29 publications
8
89
0
3
Order By: Relevance
“…[36][37][38][39] Janda et al 20 desarrollaron el bacteriófago GNC92H2-p-VIII, al cual se le modificaron las proteínas de superficie pVIII, con el fin de generar una especie de malla esponjosa capaz de capturar las moléculas de cocaína dentro del SNC. La inmunización (dos veces diariamente) de ratas, vía intranasal con el bacteriófago, atenuó significativamente la actividad locomotora, pero sólo para dosis bajas o medias de cocaína.…”
Section: 31unclassified
See 2 more Smart Citations
“…[36][37][38][39] Janda et al 20 desarrollaron el bacteriófago GNC92H2-p-VIII, al cual se le modificaron las proteínas de superficie pVIII, con el fin de generar una especie de malla esponjosa capaz de capturar las moléculas de cocaína dentro del SNC. La inmunización (dos veces diariamente) de ratas, vía intranasal con el bacteriófago, atenuó significativamente la actividad locomotora, pero sólo para dosis bajas o medias de cocaína.…”
Section: 31unclassified
“…La inmunización (dos veces diariamente) de ratas, vía intranasal con el bacteriófago, atenuó significativamente la actividad locomotora, pero sólo para dosis bajas o medias de cocaína. 36,37,39 Los estudios concluyeron que la eficacia del bacteriófago GNC92H2-p-VIII para capturar a la cocaína era dependiente del número de copias generadas.…”
Section: 31unclassified
See 1 more Smart Citation
“…À , and the E3 À serotype 5 Ad vector with b-galactosidase in the expression cassette Rosenfeld et al 1992;Wee et al 2012). The Ad5bgal vector was disrupted in 0.5% sodium dodecyl sulfate at 56 1C for 45 s. The cocaine hapten GNE (0.3 mg) was activated overnight at 4 1C after the addition of 7.2 ml charging solution (2.4 mg of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and 2 mg of N-hydroxysulfosuccinimide in 4 ml H 2 O and 40 ml dimethylformamide) Wee et al 2012).…”
Section: Methods Dad5gne Vaccinementioning
confidence: 99%
“…With the goal of blocking access of cocaine to the CNS to prevent DAT occupancy levels that induce cocaine's psychotropic effects, we have developed an anti-cocaine vaccine (dAd5GNE) based on a cocaine analog covalently coupled to the capsid proteins of a disrupted serotype 5 human adenovirus Wee et al 2012). Studies in mice and rats have shown that dAd5GNE prevents cocaine-induced hyperactivity and addiction-related behavior in these species (Koob et al 2011;Hicks et al 2011;Wee et al 2012).…”
Section: Introductionmentioning
confidence: 99%